Biokinetics and Efficacy of Aminocyclopyrachlor-Methyl Ester as Influenced by Diflufenzopyr. Issue 3 (September 2014) - Vargas, Jose J.; Brosnan, James T.; Mueller, Thomas C.; Kopsell, Dean A.; Klingeman, William E.; Armel, Gregory R.
Abstract : Research studies evaluated effects of the auxin transport inhibitor, diflufenzopyr, on the biokinetics and efficacy of aminocyclopyrachlor-methyl ester (AMCP-ME) applications to black nightshade and large crabgrass. Absorption, translocation, and metabolism of 14 C-AMCP-ME was quantified with and without diflufenzopyr (35 g ai ha −1 ). Diflufenzopyr had minimal effects on translocation of radioactivity in either species. Accumulation of radioactivity in aboveground plant sections of black nightshade was greater than or equal to that in large crabgrass by 72 h after treatment (HAT). In both species, metabolism of 14 C-AMCP-ME was rapid, as 60 to 78% of the extracted radioactivity was the free acid metabolite 8 HAT. In the greenhouse, black nightshade and large crabgrass were treated with AMCP-ME (9, 18, and 35 g ai ha −1 ) alone and in combination with diflufenzopyr (35 g ha −1 ). Mixtures of AMCP-ME plus diflufenzopyr did not increase large crabgrass control compared with AMCP-ME alone at any time. Diflufenzopyr (35 g ha −1 ) increased black nightshade control with AMCP-ME (18 and 35 g ha −1 ) 7 d after treatment (DAT). However, this increase in control was not observed 14 or 28 DAT. All treatments containing AMCP-ME controlled large crabgrass 70 to 79% 28 DAT compared with > 93% for black nightshade at the same time point.